PENGARUH PENGEMBANGAN CITY WALK TEGAL TERHADAP OKUPANSI HOTEL - Lourensius Hendra Putra; Prasetya Putra Nugraha; Abdul rohman marbun (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to analyze the impact of the City Walk development on hotel occupancy rates in Tegal City, focusing on the influence of perception, price, distance, and promotion on occupancy changes after the development. A quantitative approach was employed through a survey of 100 respondents consisting of hotel managers or administrators, with data analyzed using descriptive and inferential statistics, including normality, multicollinearity, and heteroscedasticity tests, paired t-test, and multiple linear regression. The findings reveal a significant difference in occupancy rates before and after the City Walk development (p < 0.01), with an average increase of 1.88%. Regression analysis showed an R² value of 0.482 and an F-statistic of 21.53 (p < 0.001), indicating that the four variables collectively explained 48.2% of the variation in occupancy rates, with perception, price, and promotion having a significant positive effect, while distance had a significant negative effect. These results highlight that hotel management strategies integrating a positive City Walk image, competitive pricing, accessible location, and effective promotion can significantly enhance occupancy rates.